ANALISIS HARGA POKOK PRODUKSI, LABA USAHA, DAN PERMINTAAN AYAM RAS PEDAGING PROBIOTIK DI KOTA METRO - Andini Fitria Hadi; R Hanung Ismono; Helvi Yanfika (Lampung University, 2015)
This study aims to analyze the main production cost of probiotic and non probiotic broilers, the profit of probiotic and non probiotic broilers business, and the influencing factors on the demand of probiotic broilers. The research data was collected in September 2014. The research was conducted in Central Metro and North Metro Subdistrict of Metro City. These locations were chosen purposively and the samples were drawn by purposive sampling method. Samples consisted of eight broilers breeders and 33 consumers of probiotic broilers. The data was analyzed quantitatively by full costing and variable costing methods to the main production cost and profit, and multiple linear regression analysis for the influencing factors on the demand. The results of this research showed that the main production cost of probiotic broilers was higher than non probiotic broilers. The full costing method showed that the main production cost of probiotic broilers and non probiotic broilers were Rp16,329.06 and Rp15,824.37. The variable costing method showed that the main production cost of probiotic broilers and non probiotic broilers were Rp15,409.74 and Rp14,932.55. The profit of probiotic broilers was lower than non probiotic broilers, which was probiotic broilers Rp922,542.19 and non probiotic broilers Rp1,238,754.05. The factors which influenced the demand of probiotic broilers were the price of probiotic broilers, price of non probiotic broilers, price of range chickens, number of family members, and health knowledge. Key words: broilers, demand, main production cost, probiotic, profit